2018
DOI: 10.1007/s00418-018-1685-6
|View full text |Cite
|
Sign up to set email alerts
|

Wharton’s jelly-derived mesenchymal cells as a new source for the generation of microtissues for tissue engineering applications

Abstract: Microtissues (MT) are currently considered as a promising alternative for the fabrication of natural, 3D biomimetic functional units for the construction of bio-artificial substitutes by tissue engineering (TE). The aim of this study was to evaluate the possibility of generating mesenchymal cell-based MT using human umbilical cord Wharton's jelly stromal cells (WJSC-MT). MT were generated using agarose microchips and evaluated ex vivo during 28 days. Fibroblasts MT (FIB-MT) were used as control. Morphometry, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Agarose Hydrogel Preparation, Cytotoxicity Assay, and Microtissue Formation. Hydrogels of 3% type IX-A agarose were prepared as previously described [67], with minor modifications, and allowed to solidify for 48 h (Figure 1(a)). Cytotoxicity of the agarose hydrogel was tested using the MTS assay (CellTiter 96 Aqueous One Solution Cell Proliferation Assay, Promega, Spain).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agarose Hydrogel Preparation, Cytotoxicity Assay, and Microtissue Formation. Hydrogels of 3% type IX-A agarose were prepared as previously described [67], with minor modifications, and allowed to solidify for 48 h (Figure 1(a)). Cytotoxicity of the agarose hydrogel was tested using the MTS assay (CellTiter 96 Aqueous One Solution Cell Proliferation Assay, Promega, Spain).…”
Section: Methodsmentioning
confidence: 99%
“…Several polymers, such as PLA (polylactic acid), PCL (polycaprolactone), PEGMA (poly(ethylene glycol)methacrylate), and gelatine, among others, have been used to create suitable hydrogels or nanofiber-based scaffolds with adequate physical properties to promote chondrogenic differentiation [72][73][74][75]. However, also numerous studies are currently focused on the development of organoids, creating organomimetic tissues [67,[76][77][78], which mimic and improve the functions of the native tissues where they will be implanted. Our results agree with those of Torras et al, who reported that pluripotent cells, as DPSCs, have a high capability for intrinsic organization when cultured in an organoid or microtissue model, which is related to different cell functions, such as extracellular matrix synthesis, among others [76].…”
Section: Stem Cells Internationalmentioning
confidence: 99%
“…To determine the ex vivo biocompatibility of the bioengineered dermal skin substitutes, SS and FSS were kept under standard culture conditions for 24 h and 48 h. After each time point, cell death was assessed by quantifying free DNA released from ruptured cells to the culture medium using a NanoDrop 2000 UV–Vis Spectrophotometer (Thermo Fisher Scientific) as previously described [ 29 ]. In addition, cell function was analyzed by quantifying the mitochondrial dehydrogenase activity in live cells using the cell proliferation and viability reagent WST-1 (Roche Diagnostics, Mannheim, Germany) [ 29 ]. In both cases, live cells grown in basal medium were used as positive controls (CTR +), whilst cells incubated in 1% triton X-100 were used as negative controls (CTR–).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the ex vivo biocompatibility of the bioengineered dermal skin substitutes, SS and FSS were kept under standard culture conditions for 24 h and 48 h. After each time point, cell death was assessed by quantifying free DNA released from ruptured cells to the culture medium using a NanoDrop 2000 UV-Vis Spectrophotometer (Thermo Fisher Scienti c) as previously described (29). In addition, cell function was analyzed by quantifying the mitochondrial dehydrogenase activity in live cells using the cell proliferation and viability reagent WST-1 (Roche Diagnostics, Mannheim, Germany) (29). In both cases, live cells grown in basal medium were used as positive controls (CTR+), whilst cells incubated in 1% triton X-100 were used as negative controls (CTR-).…”
Section: Ex Vivo Analysis Of Biocompatibility Of Fssmentioning
confidence: 99%